Distribution of imported malaria cases in a non-endemic municipality of Northeast of Antioquia (Colombia), 2008-2013 (2023)
Introduction: Imported malaria is a problem of public and individual health, due to its high mortality and presentation of nonspecific signs and symptoms that hinder early diagnosis and timely treatment. Objective: To characterize the distribution of imported malaria cases in nonendemic municipality of Northeast of Antioquia, 2008-20013. Methods: Cross-sectional study in patients with confirmed diagnosis of imported malaria. The description of the population was performed using summary measures and frequencies, the percentage distribution of Plasmodium species were compared with the baseline characteristics of the group through the chi square test. Results: 73 patients were included with a mean age of 30 years; the main occupations were mining (47.9[%]) and agriculture (38.4[%]). 82.2[%] were infected by Plasmodium vivax and Plasmodium falciparum at 17.8[%]. The distribution of parasite species did not show statistical differences by the group characteristics. Conclusion: The percentage distribution of the species of P. vivax and P. falciparum are consistent with the epidemiological profile of the region; this study confirms that occupation, sex and age are factors of great interest in the study of imported malaria in the region. © iMedPub.